Rhizospheric Microbiome Responses to Cover Crop Suppression Methods - Marianela E. Morales; Marco Allegrini; Gastón A. Iocoli; Jessica Basualdo; María B. Villamil; María C. Zabaloy (Agronomy, 2022)
Although winter cover crops (WCCs) have demonstrated positive effects on soil properties, relatively little is known about the responses of the soil and plant microbiomes to the introduction of WCCs and their associated management. Our objective was to evaluate the effects of WCC suppression methods on the rhizosphere microbiome of oats under field conditions. Rhizospheric soil was extracted to quantify the abundances of amoA gene of ammonia-oxidizing bacteria and archaea, and nitrite reductase genes (nirK and nirS), and to determine potential nitrification activity. The bacterial 16S rRNA V4 region and fungal ITS regions were sequenced with the Illumina MiSeq system. Overall, our results indicated that the composition of the bacterial and fungal communities of the rhizosphere were sensitive to the WCC suppression methods. Some bacterial genera, including fungal antagonists and chitin degraders, and two fungi associated with plant potential pathogens, were favored by both suppression methods, yet both methods negatively affected other genera associated with plant growth promotion characteristics. Our work contributes to a more complete understanding of the interactions between WCC management practices, soil properties, and microbial communities in the rhizosphere, which is essential for choosing management strategies that maintain soil health and promote environmental sustainability.